2018
DOI: 10.1080/19336896.2018.1534485
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic characterization for the denatured state of bovine prion protein and the BSE Associated variant E211K

Abstract: Propagation of transmissible spongiform encephalopathies involves the conversion of cellular prion protein, PrPC, into a misfolded oligomeric form, PrPSc. The most common hereditary prion disease is a genetic form of Creutzfeldt-Jakob disease in humans, in which a mutation in the prion gene results in a glutamic acid to lysine substitution at position 200 (E200K) in PrP. In cattle, the analogous amino acid substitution is found at residue 211 (E211K) and has been associated with a case of bovine spongiform enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…However, E200K‐mutant human PrP exhibited nearly identical features, including flexible regions and backbone structure of human PrP, compared to wild‐type human PrP. Similar to E200K‐mutant human PrP, E211K‐mutant bovine PrP also showed minor differences in thermodynamic characteristics (Hwang & Nicholson, 2018). However, previous studies have reported that the E200K mutation of human PrP could influence impairment of copper‐binding capacity, confer susceptibility to copper and be accompanied by oxidative damage (Canello et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, E200K‐mutant human PrP exhibited nearly identical features, including flexible regions and backbone structure of human PrP, compared to wild‐type human PrP. Similar to E200K‐mutant human PrP, E211K‐mutant bovine PrP also showed minor differences in thermodynamic characteristics (Hwang & Nicholson, 2018). However, previous studies have reported that the E200K mutation of human PrP could influence impairment of copper‐binding capacity, confer susceptibility to copper and be accompanied by oxidative damage (Canello et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Prion diseases are a group of deadly neurological diseases due to the improper folding of the cellular prion protein (PrPC) inta a pathogenic form (PrP SC ), mainly in the brain, but also in other tissues [1]. The PrP SC protein may cause incorrect folding of subsequent PrP C proteins and cause various diseases in the same host species [2,3]. Prion diseases affect both humans and various animals.…”
Section: Introductionmentioning
confidence: 99%
“…These include scrapie and goat scrapie, bovine spongiform encephalopathy, chronic, debilitating deer disease and Creutzfeldt-Jacob disease in humans. These disorders can be sporadic, inherited, or acquired by infection [2].…”
Section: Introductionmentioning
confidence: 99%